Pengaruh Pelayanan, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada Dinas Tenaga Kerja dan Perindustrian Kabupaten Labuhanbatu Utara - Yusliana Saragih; Syaiful Bahri; Muis Fauzi Rambe; Darma Aditya (Journal on Education, 2023)
This study aims to determine simultaneously and partially the effect of service, job satisfaction and work motivation on employee performance at the Department of Labor and Industry of North Labuhanbatu Regency. The population used in this study were all employees of the Department of Labor and Industry of North Labuhanbatu Regency. While the sampling technique used the census method, namely taking all members of the population as a research sample totaling 32 people. The analytical model used in this study is Descriptive Analysis and Path Linear Regression Analysis with the SPSS for Windows 22.0 program. The results of the study found that service had an effect on employee performance, as evidenced by the tcount value of 4.450 > ttable 1.685 and a significance level of 0.000 <0.05. Job satisfaction affects employee performance, as evidenced by the tcount value of 5.507 > ttable 1.685 and a significance level of 0.000 <0.05. work motivation affects employee performance, as evidenced by the tcount value of 4.276 > ttable 1.685 and a significance level of 0.000 <0.05. And service, job satisfaction and work motivation simultaneously affect employee performance, as evidenced by the Fcount value of 5.299 > Ftable of 2.96 and a significance value of 0.000 <0.05. The contribution of service variables, job satisfaction and work motivation to employee performance at the Department of Labor and Industry of North Labuhanbatu Regency is 50.1%, the remaining 49.8% of employee performance is influenced by other variables.